Fotokonduktor Al-GaN-Al untuk Aplikasi Detektor Ultraviolet - Dadi Rusdiana (Jurnal Matematika & Sains, 2008)
An ultraviolet detector has been fabricated from a GaN thin film with Al-GaN-Al photoconductor structure. The I-Vcharacterization on the photoconductor samples under irradiation condition indicates an increase in the electronconcentration to 4.6 Ã 1018 cm-3 with photoconductivity of 59.9 Î©-1cm-1, whereas under dark condition thephotoconductivity is 45.7 Î© -1cm-1. There is an increase in the conductivity by about 14.2 Î©-1cm-1 as a result fromirradiation by photons with energy 3.4 eV. The I-V curve also yields a contact resistance of around 0.26 Î©cm3 withbarrier height between aluminum and GaN of 0.44 eV in dark condition, whereas with irradiation the barrier reduces to0.43 eV. The low contact resistance indicates that aluminum contact has an ohmic contact characteristic with type-nGaN semiconductor. The measurements on spectral responses of the photoconductor samples show that the samples arequite sensitive to light with wavelength between 345 nm and 365 nm which is in ultraviolet range. For wavelengthlonger than 365 nm the current response drops significantly. This suggests that the samples have a cutoff wavelength Î»cof about 365 nm.